Associations between participation in a Physical Activity-Based Positive Youth Development Program and Academic Outcomes. (December 2019) - McDavid, Lindley; McDonough, Meghan H.; Wong, Janet B.; Snyder, Frank J.; Ruiz, Yumary; Blankenship, Bonnie B.
Abstract: Introduction: Physical activity-based positive youth development (PYD) programs offer asset building experiences to foster the overall well-being of youth. These programs have the potential to enhance success in other important contexts for children, such as school. However, rigorous examination of this potential impact is needed. Methods: Propensity score matching was used to compare school outcomes among children who participated in a short, summer physical activity-based PYD program in the USA and children who were from similar backgrounds and from the same school district but did not attend the program. The sample included 149 pairs of students aged 7–12 years ( M  = 10.11, SD  = 1.26) and, in each group, 62% were from ethnically diverse backgrounds, 38% were from primarily Caucasian backgrounds, and 80 were female and 69 were male, and birth years were equally distributed. Ordinal and logistic regression models were used to test for differences between standardized math and language arts test scores, excused and unexcused absences, and total suspensions and expulsions between the two groups. Results: PYD program youth had 55% and 46% greater odds being in the highest math (χ 2 (1, N  = 298) = 4.06, p  = .04) and total days attended categories (χ 2 (1, N  = 298) = 5.58, p  = .02) respectively. No other significant differences were found. When using a more rigorous quasi-experimental and longitudinal design, participation in a PYD program predicted some but not all academic performance and behaviors. PYD programs may need to be designed to specifically nurture academic skills to consistently impact academic outcomes.